PENDEKATAN KETERAMPILAN PROSES DALAM PEMBELAJARAN IPA MAHASISWA PGSD - Syofyan, Harlinda (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2020)
Teaching is an art, and the teacher as a planner of all activities in the class must be able to provide varied teaching. In addition to avoiding monotonous teaching, there are also demands to activate students in learning. So that students of school teacher education are trained in teaching science with a different approach in every practice or simulation of each activity in the classroom. The purpose of this study was to determine the ability of PGSD students to apply the process skills approach in implementing simulations in science learning classes. This study uses descriptive qualitative methods and data sources data from the assessment of lesson plans and simulations in front of the class. Data collection techniques began with an assessment of the learning implementation plan they made and compared with the results of the simulation they did. The material used is energy subject material at grade IV elementary school. The results of the assessment of the Learning Implementation Plan found that 70% with good criteria, and 30% with sufficient criteria, and the average assessment was 80.40. And from the simulation results obtained 39% run Learning Implementation Plan with the process skills approach with excellent categories, 31% with good categories, 23% are sufficient categories, but there are still 8% who run simulations in the poor category, and an average rating of 80, 71.